Spaceborne Optical Switching Technology for Satellite Internet - Jiacheng MENG; Ningbo XIE; Zhaofeng BAI; Jiaxuan ZHU; Junxia WU; Duorui GAO; Wei WANG; Xiaoping XIE (天地一体化信息网络)
With the increasing demands for ultra-high speed and large-capacity information transmission such as satellite remote sensing, big data super computing center, video battlefield and 6G mobile communication.The satellite laser communication technology using laser instead of traditional microwave as information carrier has become development trend.It is an eff ective mean to solve the bottleneck of microwave communication bandwidth and reduce the shortage of spectrum resources.In the future, we need to build a satellite internet with global coverage, which are needed to provide the capabilities that terrestrial optical fi ber networks do not have (large coverage, low-delay, services in sparsely populated areas, no geographical obstacles, etc.).The spaceborne optical switching technology is the key and core for the ultra-high speed and large capacity information processing on satellite nodes.Firstly, the development context of satellite internet based on laser communication was introduced, the importance of spaceborne optical switching technology for satellite internet was analyzed.It focused on the detailed classifi cation and comparison, system and information processing mode of space-borne optical switching technology, and showed the potential technical scheme in the future.Then, the characteristics and application schemes of optical switching core devices were analyzed and studied to provided reference for the next generation of satellite internet technology research.